Megalopolis and the Achaian koinon: local identity and the federal state - Close, Elke (The University of Edinburgh, 2018)
This dissertation examines the relationship between the Arkadian city of Megalopolis and the Achaian koinon in the Hellenistic period. By arguing that Megalopolis was a polis which used its own local identity to carve out a prominent position for itself within the Achaian federation, this thesis is able to provide new insights into the study of the wider topic of the relationship between federations and their member states. To support this argument, the thesis is divided into three parts. In part one of the dissertation, the Megalopolitan identity is clearly established by identifying its basic components, which were the result of the city’s foundation by the Arkadian koinon around 368 BC as well as its Achaian membership of 235 BC. The Megalopolitan identity was marked by a complex structure; it was characterised by a deep and traditional hatred for Sparta, longstanding relations with the Macedonian kings, a clear understanding of the mechanisms of a federal state and multi-ethnic politics, and, by Polybius’ time, a connection to both Arkadia as well as Achaia. The second part examines the influence of this local identity on the koinon through the direct relationship of Megalopolis with the federal government via its Achaian membership. Within the Achaian League, Megalopolis was an active member, taking part in the federal institutions and minting coins. However, through its interactions with other members of the federal state, Megalopolis used its relationship with the federal state to its own advantage. Finally, the last part of the thesis explores the role of Megalopolis and its local interests in Achaian foreign politics. The polis seems to have influenced these through the emergence of a series of influential statesmen (such as Philopoimen and Lykortas) as well as several new policies pursued by the Achaians after Megalopolis’ membership. Examples of these new policies are the Achaian alliance with Macedon of 225 BC and the increased focus of the koinon on Sparta in the second century BC, something that also shaped Achaian interactions with Rome. Throughout the thesis particular attention is paid to the narrative of the historian Polybius and the problems his writings pose, since he was an important source for the history of the Achaian koinon and who, as a Megalopolitan, was an excellent example of this distinct Megalopolitan identity. By shedding light on the various ways in which Megalopolis affected the Achaian koinon and its politics, this thesis shows that Megalopolis merits more attention than it has received in the past, as it was more than just an Arkadian city that was a member of the Achaian koinon. Furthermore, the intricate analysis of the distinct Megalopolitan identity makes a novel contribution to the wider study on the interaction between the polis, as a civic unit, and the federal state, as a developing political structure.
Keywords: Megalopolis; Polybius; federalism; Hellenistic; Peloponnese; Arcadia; Achaia; koinon; federation